2007
DOI: 10.1108/17466660200700022
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of the effectiveness of a programme of multisystemic treatment (MST) across participant groups in the second year of operation

Abstract: In order to examine the sustainability of programme effectiveness, we investigated whether the effects of multisystemic treatment (MST) on a second group of adolescents would match those reported in an earlier randomised controlled trial (RCT). Pre‐ and post‐treatment assessments were analysed in a participant group of 105; 55 youths were referred to MST in the programme's second year of operation (MST2), and 50 youths were included in the RCT the first year in which 30 were randomly assigned to MST (MST1) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…Research on the effectiveness of MST in the USA has shown positive short-term and long-term results, when compared with alternative treatments, in reducing criminal behavior and violence, substance abuse, and serious emotional disturbance, as well as improving family relations and functioning (Borduin et al, 1995;Curtis, Ronan, & Bordouin, 2004;Henggeler et al, 1997Henggeler et al, , 2006Henggeler & Brondino, 1992;Henggeler, Pickrel, & Brondino, 1999;Schaeffer & Borduin, 2005;TimmonsMitchell, Bender, Kishna, & Mitchell, 2006). Similar positive short-term (Ogden & Halliday-Boykins, 2004) and long-term (Ogden & Amlund Hagen, 2006;Ogden, Amlund Hagen, & Andersen, 2007) treatment results have been reported from Norway. In Canada, however, successful replication of treatment results has not been achieved (Cunningham, 2002).…”
Section: Introductionsupporting
confidence: 86%
“…Research on the effectiveness of MST in the USA has shown positive short-term and long-term results, when compared with alternative treatments, in reducing criminal behavior and violence, substance abuse, and serious emotional disturbance, as well as improving family relations and functioning (Borduin et al, 1995;Curtis, Ronan, & Bordouin, 2004;Henggeler et al, 1997Henggeler et al, , 2006Henggeler & Brondino, 1992;Henggeler, Pickrel, & Brondino, 1999;Schaeffer & Borduin, 2005;TimmonsMitchell, Bender, Kishna, & Mitchell, 2006). Similar positive short-term (Ogden & Halliday-Boykins, 2004) and long-term (Ogden & Amlund Hagen, 2006;Ogden, Amlund Hagen, & Andersen, 2007) treatment results have been reported from Norway. In Canada, however, successful replication of treatment results has not been achieved (Cunningham, 2002).…”
Section: Introductionsupporting
confidence: 86%
“…Many of the published RCTs have demonstrated long-term outcomes, including one showing sustained disruptive behavior outcomes for MST versus individual therapy (blend of psychodynamic, client-centered, and behavioral) at 14- and 22-years posttreatment (Sawyer & Borduin, 2011; Schaeffer & Borduin, 2005). In addition to RCTs, there have been five (nonrandomized) clinical studies of MST for justice-involved youth that evaluated disruptive behavior outcomes, all conducted independently of developers and all demonstrating positive disruptive behavior findings favoring MST (see Table 3; Curtis, Ronan, Heiblum, & Crellin, 2009; Fain, Greathouse, Turner, & Weinberg, 2014; Ogden, Hagen, & Andersen, 2007; Smith-Boydston, et al, 2014; Stambaugh et al, 2007). Notably, MST also is among the ecological family-based treatments deemed well established for treatment of adolescent substance abuse (Hogue, et al, 2014), and it has been adapted for other specific problems in adolescents and young adults (i.e., juvenile sexual offenders; youth in psychiatric crisis; youth with physical abuse; youth with chronic health conditions; emerging adults with justice involvement and mental illness).…”
Section: Resultsmentioning
confidence: 99%
“…Evaluation studies of MST in a number of different countries have been promising, including a relatively low drop-out rate and benefits maintained at follow-up [32,37]. MST has also shown to be effective for young people with substance misuse disorders [32], which is an important consideration in view of the high prevalence rate in persistent offenders.…”
Section: Service Implicationsmentioning
confidence: 99%